2019
DOI: 10.1177/0023677219881481
|View full text |Cite
|
Sign up to set email alerts
|

A safe bet? Inter-laboratory variability in behaviour-based severity assessment

Abstract: Evidence-based severity assessment is essential as a basis for ethical evaluation in animal experimentation to ensure animal welfare, legal compliance and scientific quality. To fulfil these tasks scientists, animal care and veterinary personnel need assessment tools that provide species-relevant measurements of the animals' physical and affective state. In a three-centre study inter-laboratory robustness of body weight monitoring, mouse grimace scale (MGS) and burrowing test were evaluated. The parameters wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 27 publications
(45 reference statements)
1
21
0
Order By: Relevance
“…A further important outcome from Miller and Leach [ 58 ] was that there was no effect of repeatedly being placed in the photography boxes on grimace score i.e., a habituation effect over the three occasions used [ 58 ]. The later study by Jirkof et al [ 85 ] in 2020 supports this finding. This provides assurance that longitudinal monitoring post-procedure could occur throughout the day without the need to account for time of day or habituation to the box.…”
Section: Clinical Applicability Of Grimace Scales In Biomedical Rementioning
confidence: 69%
See 1 more Smart Citation
“…A further important outcome from Miller and Leach [ 58 ] was that there was no effect of repeatedly being placed in the photography boxes on grimace score i.e., a habituation effect over the three occasions used [ 58 ]. The later study by Jirkof et al [ 85 ] in 2020 supports this finding. This provides assurance that longitudinal monitoring post-procedure could occur throughout the day without the need to account for time of day or habituation to the box.…”
Section: Clinical Applicability Of Grimace Scales In Biomedical Rementioning
confidence: 69%
“…There is also some evidence of inter-laboratory variation in the outputs obtained from behavioral testing, to include MGS scores. In a multicenter study, Jirkof et al [ 85 ] in 2020 demonstrated some quantitative differences in scores, although they were qualitatively comparable (direction of effect). However, variability between research centers in the MGS, especially when presented as a median score, was less pronounced than in burrowing behavior readouts [ 84 ].…”
Section: Clinical Applicability Of Grimace Scales In Biomedical Rementioning
confidence: 99%
“…a habituation effect over the 3 occasions used 58 . The later study by Jirkof et al 85 in 2020 supports this finding. This provides assurance that longitudinal monitoring post-procedure could occur throughout the day without the need to account for time of day or habituation to the box.…”
Section: Environmental Impactsmentioning
confidence: 74%
“…There is also some evidence of inter-laboratory variation in the outputs obtained from behavioural testing, to include MGS scores. In a multicenter study, Jirkof et al 85 in 2020 demonstrated some quantitative differences in scores, although they were qualitatively comparable (direction of effect). However, variability between research centers in the MGS, especially when presented as a median score, was less pronounced than in burrowing behavior readouts 84 .…”
Section: Environmental Impactsmentioning
confidence: 94%
“…59 Therefore, again, standardization is crucial as assessment protocols may vary between laboratories, resulting in the lack or changed manifestation of these behaviours (Schwabe et al, this issue; Jirkof et al, this issue). 60,61 Another motivational-or emotionaldriven behaviour, namely voluntary wheel running, has been utilized to assess the severity of experimental procedures. 62 Benefits include an observer-independent, automatized assessment of severity that has been proposed to serve as an indicator of disturbed wellbeing (Mallien et al, this issue).…”
Section: Techniques To Assess Severity: Balancing Burden Bias and Bementioning
confidence: 99%